Youth voice in service acceptability: Experiences of lesbian, gay, bisexual, and transgender adolescents. Issue 3 (3rd July 2018) - Ott, Vivian E.
ABSTRACT: This study engaged lesbian, gay, bisexual, and transgender (LGBT) youths to tell their stories of satisfying and dissatisfying HIV-related service features and tapped into their common language when expressing satisfaction. Findings included youth agreement with six of the nine features proposed by adult experts and identification of "atmosphere, " the service feature encompassing the youths' need to be themselves, to find comfort, and to socialize. Inclusion of youth voice in the design of a satisfaction survey highlighted those features most meaningful to these LGBT youths and added to the growing literature regarding power sharing with youths in health services evaluation.